From Knowledge to Adherence: Implementing Health Promotion Model in Hypertension Self-Management Education - Ika Listyorini, Puguh; Witriyani, Witriyani; Latifa Noor, Hesty (LPPM Universitas Duta Bangsa Surakarta, 2025)
Hypertension is a major global health problem and a leading risk factor for cardiovascular diseases, stroke, and kidney failure. Despite the availability of effective treatment, patient adherence to hypertension management remains low, particularly in primary health care settings. This study aimed to evaluate the effectiveness of Health Promotion Model (HPM)-based Self-Management Education (SME) in improving adherence and reducing blood pressure among hypertensive patients in Kunduran, Blora, Indonesia. A quasi-experimental design with a control group was conducted involving 60 respondents, divided equally into intervention and control groups. The intervention group received SME sessions integrating education, over four weeks, while the control group received standard care. Data were collected using an adherence questionnaire and digital sphygmomanometer before and after intervention. Results showed a significant improvement in adherence scores in the intervention group (pre-test: 62.3 ± 8.5; post-test: 75.6 ± 7.9; p < 0.001), whereas the control group demonstrated no significant change (p = 0.224). Moreover, the intervention group experienced a greater reduction in both systolic and diastolic blood pressure compared to the control group (p < 0.05). These findings suggest that HPM-based SME is an effective strategy to enhance adherence and blood pressure control in hypertensive patients within primary care settings.